PERTIMBANGAN HAKIM PENGADILAN AGAMA MEMUTUS PERKARA PERCERAIAN DISERTAI HAK ASUH ANAK - Albariq Ivan Nanda (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTThe iSociety iis iinseparable ifrom ithe ilaw, iranging ifrom inorms, ivalues, imanners iand ietiquette ito ithe ilaws iand iregulations iin ithe ijudiciary. iDivorce iitself iis ione iform iof ilegal ievents iin ithe icommunity. iThe iformulation iof ithe iproblem iin ithis ijournal iare: i1) iWhat iis ithe ibasis ifor ithe iconsideration iof iMalang iCity iReligious iCourt iJudges ito idecide idivorce icases i? i2) iHow idid ithe iMalang iCity iReligious iCourt iJudge idecide ion ia ichild icustody icase iafter ideveloping ithis iability i? iThe iresearch imethod iof ithis ijournal iis inormative ijuridical. iThe iconclusion iof ithis istudy iis ithat iMalang iCity iReligious iCourt ijudges iin ideciding idivorce icases ieven ithough ibeyond ithe ireasons istated iin ithe ilaw ialways irefer ito ithe ilaws iand iregulations iand ilook iat iother ifactors iunderlying ithe idivorce.Keywords: iDivorce, iChild iCustody, iJudge, iReligious iCourt iof iMalang iCity ABSTRAKMasyarakat itidak ibisa iterlepas idari ihukum, imulai idari inorma, inilai, itata idan ikrama ihingga ihukum iperundang-undangan idalam iperadilan. iPerceraian isendiri imerupakan isalah isatu ibentuk iperistiwa ihukum idi imasyarakat. iRumusan imasalah idalam ijurnal iini iadalah: iApa iyang imenjadi idasar ipertimbangan iHakim iPengadilan iAgama iMalang imemutus iperkara iperceraian i?; iBagaimana iputusan iHakim iPengadilan iAgama iMalang imemutus iperkara itentang iHak iAsuh iAnak i? iMetode ipenelitian ijurnal iini iadalah iyuridis inormatif. iKesimpulan ipenelitian iini iadalah ihakim iPengadilan iAgama iMalang idalam imemutuskan iperkara iperceraian imeski idiluar ialasan iyang iada idalam iundang-undang iselalu iberpatokan idalam iperaturan iperundang-undangan idan imelihat ifaktor ilain iyang imelatarbelakangi isuatu iperceraian itersebut.Kata iKunci: iPerceraian, iHak iAsuh iAnak, iHakim, iPengadilan iAgama iMalang.